(untitled) (Journal of Chemical Engineering, 2013)
The natural gas consuming sectors in Bangladesh are: i) Power, ii) Fertilizer, iii) Industry, iv) Captive power, v) Domestic, vi) Commercial, and vii) Transportation (CNG). Broad sectoral consumptions are reported in various literatures and reports, however, further breakdown of the data are difficult to find, and neither reported. The combined consumption of fertilizer, industry and captive power sectors is a significant portion of national gas consumption. This paper presents for the first time an in-depth analysis of the industrial sector gas consumption. Data were collected for each type of industry, and grouped according to the United Nations Framework Convention for Climate Change (UNFCCC). Captive generation is included in the industrial sector consumption, unlike the usual practice of considering it under the power generation. It is noticed that garments, textile and leather industries together have shown remarkable growth in the last decade. All the industries are more or less related to the national GDP growth. Some are export oriented while others address the internal market. Therefore analysis presented here should be helpful for policy makers to prioritize the sectors in case preferential supply and tariff adjustments become necessary. DOI: http://dx.doi.org/10.3329/jce.v27i1.15846 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 1-7